Gut lumen-targeted oral delivery system for bioactive agents to regulate gut microbiome - Junyu Liu; Xiaobin Li; Xiaopeng Zhang; Runming Wang; Sanyang Han; Peiwu Qin; Xin-Hui Xing; Canyang Zhang (Journal of Future Foods, 2022)
Gut microbiome (GM) is closely related to the overall health status for the human being. The dysfunction of microbiome can lead to many diseases such as inflammation, cancer and neurodegenerative disease. Therefore, it's of great importance to develop effective strategy to regulate GM. Gut lumen-targeted oral delivery system (GLT-ODS) has been extensively investigated and widely used in food science and engineering in these years, due to the targeted delivery property, controlled release profile, high biocompatibility and enhanced bioavailability of cargos. Herein, we comprehensively summarized the current advances in GLT-ODS for bioactive agent. Specifically, we systematically summarize the GLT-ODS for pre-agents (prebiotics and probiotics) and anti-agents (antibiotics and bacteriophages) according to the type of cargos. Through in-depth discussion of representative researches, we refined the limitations of existing research in carrier material and target selection, and drew a blueprint for the future technological research and development. We believe that GLT-ODS will become a safe, efficient, simple and precise GM management strategy for improvement of health and shine in the development of precision food and pharmaceutical engineering in future.